Breast Cancer Risk Factors According to Menopausal Status - Preeti Chauhan; Ritu Yadav; Vivek Kaushal (Online Journal of Health & Allied Sciences, 2017)
BACKGROUND: Breast cancer is the most common cancer worldwide. The incidence and mortality rate is increasing in developing countries as compare to developed countries. The aim of this study was to evaluate the breast cancer risk factors in premenopausal and post-menopausal women. METHODOLOGY: In the present study, two hundred breast cancer patients and one hundred age matched controls were taken to study breast cancer risk factors. The odd Ratio (ORs) at 95% confidence interval (CIs) was computed to study significance of risk factor on menopausal status. RESULTS: The mean age for menopause was 46.52±4.72 for breast cancer cases and 45.9±4.29 for control group was observed. The marital status, parity, age at menarche at =13 years was found to be associated with breast cancer risk in premenopausal age group. Early age at first full term pregnancy, number of children more than three and lactation duration of more than one year were observed to be protective factors in both pre and postmenopausal age groups A history of spontaneous abortion had no significant effect on the risk of breast cancer diagnosed before or after menopause. The positive association of breast cancer was observed for Height, weight and body mass index (BMI) in postmenopausal women. CONCLUSION: In conclusion, present results suggest that changes in reproductive pattern, menstruation and anthropometric measurements contribute to the risk of breast cancer in both pre and post-menopausal women. Further genetic and hormonal relationship based studies have been suggested using a large cohort.